2004
DOI: 10.1007/s00299-003-0705-7
|View full text |Cite
|
Sign up to set email alerts
|

Flavanol binding of nuclei from tree species

Abstract: Light microscopy was used to examine the nuclei of five tree species with respect to the presence of flavanols. Flavanols develop a blue colouration in the presence of a special p-dimethylaminocinnamaldehyde (DMACA) reagent that enables those nuclei loaded with flavanols to be recognized. Staining of the nuclei was most pronounced in both Tsuga canadensis and Taxus baccata, variable in Metasequoia glyptostroboides, faint in Coffea arabica and minimal in Prunus avium. HPLC analysis showed that the five species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 15 publications
(17 reference statements)
1
49
0
4
Order By: Relevance
“…This observation is consistent with characteristics of other plant species that showed flavonoid and ROS accumulation in the nuclei (Feucht et al, 2004;Mazars et al, 2010;Lewis et al, 2011). Immunolocalization with antibodies against CHS and chalcone isomerase suggests that the enzymes of flavonoid synthesis are localized to the nucleus in Arabidopsis roots (Saslowsky et al, 2005).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This observation is consistent with characteristics of other plant species that showed flavonoid and ROS accumulation in the nuclei (Feucht et al, 2004;Mazars et al, 2010;Lewis et al, 2011). Immunolocalization with antibodies against CHS and chalcone isomerase suggests that the enzymes of flavonoid synthesis are localized to the nucleus in Arabidopsis roots (Saslowsky et al, 2005).…”
Section: Discussionsupporting
confidence: 75%
“…This image indicated that we can resolve these two fluorescent signals and that flavonols accumulated in the cytosol, but not the chloroplasts of guard cells. It was also evident that DPBA fluorescence was greater in the regions of the guard cell that appeared to be nuclei, a cellular location that exhibited flavonoid accumulation in other plant cells types (Feucht et al, 2004;Saslowsky et al, 2005;Lewis et al, 2011). Verification of nuclear flavonol accumulation was completed by simultaneously imaging DPBA and Hoechst 33258, a nucleic acid stain (Supplemental Fig.…”
Section: Flavonols and Their Biosynthetic Machinery Are Found In Guarmentioning
confidence: 99%
“…The exclusive localization of G1 to nuclei was surprising, although free or substituted flavanols or flavonols have been localized to plant nuclei (41)(42)(43), and CHS and CHI localize to nuclei in several different cell types of Arabidopsis (44). The significance of the almost exclusive presence of coumestrol and 4Ј,7-dihydroxyflavone aglycones in Medicago root nuclei is likewise not yet clear.…”
Section: Discussionmentioning
confidence: 99%
“…가로수로 쓰이는 메타쉐콰이어나무의 열 매는 폐기되고 있는데 기존의 천연염재로 사용되고 있 는 오리나무 열매와 원뿔 모양으로 유사하다. 메타세콰이어나무에는 taxodone, taxoquinone, metaseglyptorin A, metasequoia acid C, 2R-hydroxy-8, 15-isopimaradien-18-oic acid, (-)-acora-2,4,8-trien-15-oic acid, norlignans, catechin류와 같은 폴리페놀성 성분 등이 함 유되어 있다 [7][8][9][10] . 현재까지 메타세콰이어나무에 대한 연 …”
Section: 서 론unclassified